2011
DOI: 10.1002/elps.201100039
|View full text |Cite
|
Sign up to set email alerts
|

Cascade and staggered dielectrophoretic cell sorters

Abstract: We have developed two new microfluidic cell sorters based on conventional negative dielectrophoresis (DEP) for continuous flow operations. The first is a cascade configuration sorter designed to increase purity of isolated target cell. The second has two staggered side channels in opposite side walls to increase sample throughput without compromising enrichment factor. Particles (carboxylate microspheres) of different sizes were first used to demonstrate the feasibility of the present DEP sorters for cell isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…In the high-conductivity cases, the pDEP response and crossover frequency regions were fit well; the magnitude and frequency dependence, as well as the fit value for C membrane , were similar to those previously reported for other cancer cells [54][55][56]. Yang et al reported on DEP separation of LNCaPs from colorectal cancer cells, but used a higher conductivity media (σ m = 300 mS/m) at which LNCaPs experienced nDEP even in the MHz range [44]. Although we did not perform DEP characterization experiments at this conductivity, our model does predict similar nDEP behavior in those high conductivity and frequency ranges.…”
Section: Dep Characterization Of Lncapssupporting
confidence: 81%
See 2 more Smart Citations
“…In the high-conductivity cases, the pDEP response and crossover frequency regions were fit well; the magnitude and frequency dependence, as well as the fit value for C membrane , were similar to those previously reported for other cancer cells [54][55][56]. Yang et al reported on DEP separation of LNCaPs from colorectal cancer cells, but used a higher conductivity media (σ m = 300 mS/m) at which LNCaPs experienced nDEP even in the MHz range [44]. Although we did not perform DEP characterization experiments at this conductivity, our model does predict similar nDEP behavior in those high conductivity and frequency ranges.…”
Section: Dep Characterization Of Lncapssupporting
confidence: 81%
“…A majority of DEP cancer cell isolation techniques use model cancer cell lines spiked in buffer media or diluted blood; such techniques include DEP flowfield fractionation (DEP-FFF) [33][34][35][36], insulative and contactless DEP [37][38][39][40], and streamline separations using angled electrodes [41][42][43][44]. These studies separate cancer cells from other blood constituents based on their differences in DEP response in a specific applied frequency range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is defined as the ratio of target cells deflected towards the side channel to the total number of target cells flowing through the inlet. 42 g ¼ A=ðA þ BÞ;…”
Section: Quantity Analysis Of Cell Separationmentioning
confidence: 99%
“…This can be realized using a cascaded and staggered DEP sorter (demonstrated by this group) for increasing target cell purity and throughput. 42 Additionally, enriched target cells remain unaltered and can be easily cultured for further testing and analysis. Providing an improved method for early detection of pre-metastatic tumor is an important clinical goal to achieve because progression of metastatic cancer rapidly decreases survival rates.…”
Section: Potential Application In Cancer Research and Diagnosticsmentioning
confidence: 99%